ADVANTAGES OF PROJECT-BASED LEARNING IN MATHEMATICS LESSONS - Qosimova Hurriyat Shuhrat qizi (Bright Mind Publishing, 2025)
The article examines the implementation of project-based learning methods in mathematics lessons, unconventional project-based approaches to teaching, and practical effective ways of mastering complex subjects like mathematics. It presents solutions to key issues such as: implementing research processes in mathematics education, applying acquired knowledge through innovative and creative methods in real-life contexts, and utilizing modern teaching methodologies in mathematics instruction.The work describes a series of methodological approaches used to enhance the effectiveness of designing mathematics learning activities through project work. The research highlights contemporary challenges in mathematics education, including the use of modern teaching methods aligned with current demands and the application of project-based learning to facilitate mathematical comprehension.
Keywords: Project, mathematics education, project-based learning, practical education, constructive learning.